Critique, Habermas and narrative (genre): the discourse-historical approach in critical discourse studies. Issue 3 (4th May 2021) - Forchtner, Bernhard
ABSTRACT: Narratives are everywhere. We tell narratives about ourselves and we make the world meaningful through storytelling. We position others through the narratives we tell and are positioned by stories told about us. And yet, while narratives have, of course, been analysed in critical discourse studies (CDS), including in one of its most popular approaches, the discourse-historical approach (DHA), this article proposes to go a step further by systematically integrating the concept of narrative into the core of the DHA. More specifically, I consider narrative from the perspective of the concept of narrative genre. That is, I propose a focus on how meaning arises via the narrative genres of romance, tragedy, comedy and irony, i.e. through (modes of) emplotment. Such an integration does not contradict the DHA's (and CDS') focus on detailed textual analysis or reject existing foci, e.g. on argumentation, but recognises the centrality of the narrative form for social life and offers further concepts for empirical analyses. This focus on narrative genre contributes, furthermore, to the critical study of meaning-making by revising Jürgen Habermas' Critical Theory and offering a novel integration of the latter into the DHA, thus providing a theoretically justified, immanent foundation for its critique.